ISSUES AND MECHANISMS OF COMPANY’S INTERNAL INVESTMENT SOURCES FORMATION IN KEMEROVO REGION AGRO-INDUSTRIAL COMPLEX ENTERPRISES - Zotov V.P.; Kotov R.M.; Sekletsova O.V.; Dudinskaya T.K.; Shcheglova M.A. (Техника и технология пищевых производств)
One of the main goals of the companies is to form and sustain their competitive advantage for a long time. However, this can be possible if the company raises quality level, implements innovative technologies to reduce costs and enters new markets. To tackle these issues it is necessary to sustain high level and quality of fixed assets which should be up-to-date. The analysis of agricultural companies fixed assets condition revealed that they have high degree of wear and tear. The proportion of fully worn funds is increasing. The possibilities of using company’s own sources for investment in the fixed assets are limited due to the presence of unprofitable enterprises and ineffective depreciation funds formation. Depreciation has not become the source of financing replacement of fully depreciated equipment. This takes place as many companies spend accumulated depreciation charges to increase current assets. Besides, there is no depreciation fund as depreciation is added to accumulation fund and then joint resources are spent to satisfy the current needs of the company. Feasibility evaluation of the measures and ways to renew agricultural companies fixed assets and analysis of enhancing the role company’s own investment sources are the main current objectives. If one reaches them it will become possible for companies to strengthen their position in the market and be competitive in the long run.Depreciation policy aimed at increasing the role of depreciation charges as an important source of fixed assets reproduction is one of the most important measures to solve the problem of fixed assets reproduction in companies operating in agro-industrial complex.